Selective and confined growth of transition metal dichalcogenides on transferred graphene. Issue 59 (27th July 2017) - Lu, Fei; Karmakar, Arka; Shahi, Simran; Einarsson, Erik
Abstract : We demonstrate confinement of CVD grown MoS2 to a patterned graphene area, forming a vertically stacked 2D heterostructure. Abstract : We demonstrate confinement of CVD grown MoS2 to a patterned graphene area, forming a vertically stacked 2D heterostructure. The CVD-grown graphene had been transferred onto a Si wafer and patterned using photolithography. Raman mapping and spectral analysis reveal few-layer MoS2 grew selectively on graphene regions, and not on the surrounding SiO2 substrate surface. We also report CVD growth of WS2 directly on transferred graphene. Unlike MoS2, no few-layer regions were found; the WS2 was found to be either monolayer or at least five layers (bulk). The WS2 coverage was only partial, but selectivity to graphene is apparent. These findings have the potential to significantly advance fabrication of vertical 2D heterostructures and related devices, and suggest the selective growth on graphene may be applicable to TMDCs in general.